2019
DOI: 10.1097/adm.0000000000000523
|View full text |Cite
|
Sign up to set email alerts
|

Disparities Between US Opioid Overdose Deaths and Treatment Capacity: A Geospatial and Descriptive Analysis

Abstract: Introduction: With opioid-related deaths reaching epidemic levels, gaining a better understanding of access to treatment for opioid use disorder (OUD) is critical. Most studies have focused on 1 side of the equation-either provider capacity or patients' need for care, as measured by overdose deaths. This study examines the overlay between treatment program availability and opioid mortality, comparing accessibility by region. Methods: Geospatial and statistical analyses were used to model OUD treatment programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…Other studies have found that peer support intervention models have been associated with improvement in a variety of outcome measures (Bassuk, Hanson, Greene, Richard, & Laudet, 2016). There are significant gaps in access and availability to treatment programs (Langabeer et al, 2019;Rosenblatt, Andrilla, Catlin, & Larson, 2015). Lack of insurance and employment among individuals in our study further complicated access to ongoing care, since most treatment providers do not take Medicaid and state-funded programs often have excessively long wait lists, and the expansion of the state's Medicaid program for substance use disorders would be extremely beneficial for improving access to care for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that peer support intervention models have been associated with improvement in a variety of outcome measures (Bassuk, Hanson, Greene, Richard, & Laudet, 2016). There are significant gaps in access and availability to treatment programs (Langabeer et al, 2019;Rosenblatt, Andrilla, Catlin, & Larson, 2015). Lack of insurance and employment among individuals in our study further complicated access to ongoing care, since most treatment providers do not take Medicaid and state-funded programs often have excessively long wait lists, and the expansion of the state's Medicaid program for substance use disorders would be extremely beneficial for improving access to care for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the viral pandemic, MOUD waitlists were lengthy in much of Texas, which is already capacity-constrained ( Langabeer et al, 2019 ), especially for the vulnerable population who lack health insurance, employment, and financial resources. Technology can play a role in improving access and outcomes for OUD, but Ryan Haight Act regulations prohibit the use of telehealth for prescribing controlled substances during “normal” times, without rigorous processes and infrastructure ( Huskamp et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Demand for treatment far exceeds available capacity. 11 - 13 Accessible treatment options may be hard to find, as online directories are not always updated or accurate and rarely provide all options. 10 The treatment referral process in most communities has room for significant improvement.…”
Section: Introductionmentioning
confidence: 99%